Colorectal cancer in the young: clinicopathologic features and prognostic factors from a cancer institute in Peru - Ruiz, Rossana (2016)
Objective: To determine clinicopathological features and prognostic factors among young colorectal cancer (CRC) patients in a Peruvian Cancer Institute. Methods: Data of patients 40 years or younger, admitted between January 2005 and December 2010, were analyzed. Results: During the study period, 196 young patients with CRC were admitted. The tumor was located in the rectum, left colon and right colon in 45.9%, 28.6% and 25.5% of cases. Family history of CRC was found in 13.2% and an autosomal pattern of inheritance, in 8.6% of the cases. The most common symptoms were pain (67.9%) and bleeding (67.3%). The majority (63.1%) of colon cancer cases and more than a third (34.4%) of rectal cancer cases were diagnosed in stage III or IV. The histologic type was tubular, mucinous and signet ring cell adenocarcinoma in 73.5%, 14.8% and 8.6%, respectively. The depth of invasion was T3 in 21.4% and T4 in 53%. Nodal involvement was detected in 44.5%. Five-year overall survival (OS) was 44.3%. In the multivariate analysis, only the stage resulted an independent prognostic factor for survival. Conclusions: CRC in Peruvian young patients is mostly sporadic. It presents more often in the distal colon or rectum and at advanced stages of the disease. Mucinous and signet ring cell carcinoma were frequent histological types. Five-year OS stage by stage is similar to that reported in the literature for older patients. Stage was the only independent prognostic factor for survival.